Comments on the article "on the propagation of harmonic plane waves under the two-temperature theory" [P. Puri, P.M. Jordan, Int. J. Eng. Sci. 44 (2006) 1113-1126] - Mukhopadhyay S.; Kumar R.; Prasad R. (My University, 2025)
This short note presents some comments on the article "On the propagation of harmonic plane waves under the two-temperature theory" [Puri, P., & Jordan, P. M. (2006). On the propagation of harmonic plane waves under the two-temperature theory. International Journal of Engineering Science, 44, 1113-1126]. Errors in some equations and figures in this article are pointed out and their correct forms are presented. © 2011 Elsevier Ltd. All rights reserved.